Association of Ready-to-Eat Cereal Consumption with Nutrient and Food Group Intake and Diet Quality by Income Status Among Children, NHANES 2013–2016. (29th May 2020) - Smith, Jessica; Vanage, Vipra; Jain, Neha; Holschuh, Norton; Zhu, Yong
Abstract: Objectives: Ready-to-eat (RTE) cereal is an important source of nutrients and whole grains in the diet of children and is associated with higher diet quality. Socioeconomic status is also strongly associated with nutrient intake and diet quality in the US. The objective of this study was to characterize the association between RTE cereal consumption and nutrient and food group intake and diet quality in US children ages 2 to 18 years stratified by their household income status. Methods: Children age 2 to 18 years ( N  = 5658) in two cycles (2013–2014 and 2015–2016) of the National Health and Nutrition Examination Survey, a US nationally representative cross-sectional study, were categorized as RTE cereal eaters or non-eaters based on one day 24-hour dietary recall. Children were further stratified by their household income status according to the poverty-to-income ratio (PIR), as low-income (PIR ≤ 1.85), mid-income (PIR > 1.85 to <3.50) or high-income (PIR ≥ 3.50). Nutrient intakes, food group intake, and diet quality were compared between RTE cereal eaters and non-eaters in each income category using t-tests. Results: More children in the low-income group were RTE cereal eaters (52%) compared to children in the mid-income (24%) and high-income (23%) groups. RTE cereal eaters, compared to non-eaters, in the low-income group had higher intakes of calcium (23% higher), vitamin D (85%), potassium (9%), fiber (12%), iron (71%), magnesium (11%), vitamin A (66%), and vitamin C (21%) ( P  < 0.05 for all). Conversely, only intakes of vitamin D (59% higher), iron (56%) and vitamin A (39%) were significantly higher in RTE cereal eaters than non-eaters from the high-income group ( P  < 0.05 for all). Cereal eaters also had higher intake of several key food groups including total dairy, fluid milk, and whole grains in all groups ( P  < 0.05 for all). Lastly, diet quality was significantly higher among RTE cereal eaters, compared to non-eaters, in the low- and mid-income groups ( P  < 0.05 for both) but not the high-income group. Conclusions: RTE cereal is a popular, affordable food that provides under-consumed nutrients and food groups and is associated with increased diet quality particularly among low-income children. Funding Sources: This study was funded by the Bell Institute of Health and Nutrition, General Mills, Inc.